Antihyperglycemic and Hypolipidemic Activities of Flavonoids Isolated from Smilax Dominguensis Mediated by Peroxisome Proliferator-Activated Receptors - Erandi Ortiz-Barragán; Samuel Estrada-Soto; Abraham Giacoman-Martínez; Francisco J. Alarcón-Aguilar; Ángeles Fortis-Barrera; Hugo Marquina-Rodríguez; Emmanuel Gaona-Tovar; Roberto Lazzarini-Lechuga; Alfredo Suárez-Alonso; Julio César Almanza-Pérez (Pharmaceuticals, 2024)
Background/objetives: Mexican people use Smilax dominguensis as a traditional medicine for diabetes control. Some reports have shown an anti-hyperglycemic effect in animal models. In the current research, a chemical bio-guided fractionation in vitro and in silico was performed to identify compounds with anti-hyperglycemic and hypolipidemic effects through PPARγ/α dual agonist activity because they regulate genes involved in energy storage and burning, such as GLUT4 and FATP. Methods: The S. dominguensis extract was evaluated in mice through oral glucose tolerance tests. The bioactive extract was fractionated by open-column chromatography, and seven final fractions (F1–F7) were obtained and evaluated. C2C12 myoblasts were treated with the fractions, and the mRNA expression levels of PPARs, GLUT-4, and FATP were quantified. The most active fractions were evaluated on GLUT-4 translocation and lipid storage in C2C12 cells and 3T3-L1 adipocytes, respectively. Results: The F3 fraction increased the expressions of PPARγ, GLUT-4, PPARα, and FATP, and it induced GLUT-4 translocation and decreased lipid storage. F3 was then analyzed by NMR, identifying three flavonoids: luteolin, apigenin, and kaempferol. These compounds were analyzed by molecular docking and on PPAR expressions. Luteolin, apigenin, and kaempferol produced a discrete increase in the mRNA expression of PPARs. Luteolin and kaempferol also decreased lipid storage. Conclusions: Our findings indicate that the compounds identified in S. dominguensis exhibit dual agonist activity on PPARγ/PPARα and have the potential for the development of new therapeutic agents helpful in diabetes, obesity, or metabolic syndrome.